Test of Flotation Technology for a Low-sulfide Refractory Gold Ore from Qinghai - Pingtian MING; Shengping MA; Chao DING; Zhen WANG (Kuangchan zonghe liyong)
This is an article in the field of mineral processing engineering. A microfine-ultramicron refractory gold ore containing carbon and arsenic is a medium-high temperature hydrothermal altered rock type gold ore in the compressive structural fracture zone of mylonite in Qinghai Province. The main sulfide is pyrite (3.51% content), followed by arsenopyrite (1.10% content) and argillaceous mineral content 37%. Most of the gold is microscopically or ultramicroscopically dispersed in sulfide minerals such as pyrite and arsenopyrite. Gangue and limonite contain 14.43% and 8.20% of gold, respectively, and 81.04% of gold less than 0.005 mm. Based on the research of process mineralogy, this paper further optimized the flotation process parameters and reagent system, and carried out the research of the combined process of strong agitation and selective grinding, which alleviated the contradiction between fine grinding and slime of ore to a certain extent, and obtained the test indexes of gold grade of 33.06 g/t and gold recovery of 85.70%, achieving a great breakthrough in the original process index.